To find the quadratic equation that has the roots \(3+i\) and \(3-i\), we can use the fact that if \(r_1\) and \(r_2\) are the roots of a quadratic equation, the quadratic can be expressed as:
\[ x^2 - (r_1 + r_2)x + (r_1 \cdot r_2) = 0. \]
First, we calculate the sum and product of the roots:
-
Sum of the roots: \[ r_1 + r_2 = (3+i) + (3-i) = 6. \]
-
Product of the roots: \[ r_1 \cdot r_2 = (3+i)(3-i) = 3^2 - i^2 = 9 - (-1) = 10. \]
Now, substitute the sum and product into the quadratic equation form:
\[ x^2 - (6)x + (10) = 0, \]
which simplifies to:
\[ x^2 - 6x + 10 = 0. \]
Thus, the correct quadratic equation is:
\[ \boxed{x^2 - 6x + 10 = 0}. \]